Safe Motherhood Case Studies: Learning with Stakeholders in South AsiaAn Introduction - Koblinsky, Marge; Kureshy, Nazo (Journal of Health, Population and Nutrition, 2009)
doi: 10.3329/jhpn.v27i2.3323 J Health Popul Nutr 2009 April;27(2):89-92